What We Have Learned so far From Single Cell Sequencing in Acute Kidney Injury - Buse, Marc; Moeller, Marcus J.; Stamellou, Eleni (Frontiers in Physiology, 2022)
Acute Kidney injury is a major clinical problem associated with increased morbidity and mortality. Despite, intensive research the clinical outcome remains poor and apart from supportive therapy no other specific therapy exists. Single cell technologies have enabled us to get deeper insights into the transcriptome of individual cells in complex tissues like the kidney. With respect to kidney injury, this would allow us to better define the unique role of individual cell populations in the pathophysiology of acute kidney injury and progression to chronic kidney disease. In this mini review, we would like to give an overview and discuss the current major findings in the field of acute kidney injury through Single-Cell technologies.